A six‐microRNA risk score model predicts prognosis in esophageal squamous cell carcinoma. Issue 5 (1st November 2018) - Mao, Yu; Fu, Zhanzhao; Zhang, Yunjie; Dong, Lixin; Zhang, Yanqiu; Zhang, Qiang; Li, Xin; Wang, Chao
Abstract: Esophageal cancer ranks the eighth most common cancer and the sixth most common cause of cancer death worldwide. MicroRNAs (miRNAs) are small noncoding RNAs that regulate a wide variety of cancer‐related cellular processes. In the current study, a series of previously published gene expression microarray data from Gene Expression Ominus and The Cancer Genome Atlas were downloaded and further divided into training, internal, and external validation sets. Least absolute shrinkage and selectionator operator Cox regression model along with 10‐fold cross‐validation was performed to select the miRNAs associated with the prognosis of esophageal squamous cell carcinoma (ESCC) and constructed a six‐miRNA signature. Then the prediction accuracy of this signature was assessed in validation and test set using Kaplan–Meier analysis, time‐dependent receiver operating characteristic (ROC) curves and dynamic area under the ROC curve. According to the result, the prediction accuracy of miRNA signature was much better than that of tumor–node–metastasis (TNM) stage in all the three sets. Stratified analysis also demonstrated that the predict ability of this signature was independent of TNM stage. Finally, function experiments including apoptosis and colony formation assay were performed to further reveal the regulatory role of miRNAs in ESCC. Our study demonstrated the promising potential application of this novel six‐miRNA signature as an independent biomarker for survival prediction of ESCC patients. Abstract : Esophageal cancer ranks the eighth most common cancer and the sixth most common cause of cancer death worldwide. Here, we collected the data of patients with esophageal squamous cell carcinoma from both Gene Expression Ominus and The Cancer Genome Atlas and constructed a six‐microRNAs signature. Then we performed a series of function experiments to reveal the regulatory role of these miRNAs in esophageal squamous cell carcinoma.